Edisi 1 Vol 2 September 2023 MEMBANGUN UMAT DENGAN ZAKAT: Filantropi Islam Dan Pemberdayaan Ekonomi Indonesia - sukmawati, Riatun (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2023)
Islamic philanthropy is defined as voluntary action for the public good. The word philanthropy itself is actually a term popularized by people in today's modern era. Even so, the practice of philanthropy in Islam has been carried out since its inception, especially in the main guideline for Muslims, namely the Al-Quran, it turns out that there are many good deeds injunctions related to philanthropy, the three most common forms of philanthropy which are explicitly mentioned in the Al-Quran. namely zakat, infak and alms. This paper is intended to see how the concept of Islamic philanthropy improves the economy of the Indonesian people. In scientific writing, the writing method used by the author is literature study or literature review. Based on the results obtained from the literature, the authors can conclude that generous behavior such as zakat, infaq and alms has potential in developing the Indonesian economy, as well as playing a positive role in reducing poverty and social inequality. The presence of philanthropy can also be a collective effort to frame the spirit of generosity in Indonesia